EU trade policy: persistent liberalisation, contentious protectionism. Issue 3 (15th April 2016) - Bollen, Yelter; De Ville, Ferdi; Orbie, Jan
Abstract: How has EU trade policy responded to the protracted economic crisis starting in 2008? Unlike during the Great Depression of the 1930s, politicians have not resorted to protectionist measures to try to contain the downturn. The response has been just the opposite, with the dominant discourse arguing that in times of austerity and private deleveraging, trade liberalisation is indispensable for restoring growth. Adopting a historical-institutionalist perspective, we argue that the crisis has had an asymmetric effect on the two most important subsystems of EU trade policy. On the one hand, the EU took a leap forward on the path of bilateral free trade liberalisation by starting negotiations with the US, Canada and Japan. On the other hand, proposals to continue with permissive reforms for the adoption of trade defence measures and to give the EU more leverage vis-à-vis emerging economies have been blocked. We thus conclude that EU trade policy after the crisis has shown asymmetric continuity, where the liberalisation trend has been resumed more radically while accompanying defensive reforms to ease the potential pain of liberalisation have run into a stalemate.